Dukungan keluarga, kepatuhan dan pemahaman pasien terhadap diet rendah garam pada pasien dengan hipertensi - Wahid Tri Wahyudi; Risa Herlianita; Deswiyan Pagis (Holistik Jurnal Kesehatan, 2020)
Family support, adherence and understanding of a low-salt diets among patients with hypertensiveBackground: Hypertension is a disorder of the blood vessels that results in the supply of oxygen and nutrients carried by the blood blocked to the tissues of the body that needs it. Based on data from the Gedong Air Health Center, it is known that from 2015 to 2018 the incidence of hypertension fluctuated, wherein 2016 it amounted to 1962 cases but in 2017 it increased to 2814 cases and in 2018 the incidence of hypertension was 3102 cases.Purposes: Knowing the relationship of family support, adherence, and understanding of a low-salt diet among patients with hypertensiveMethod: A quantitative research designed with analysis by cross-sectional approach and the population was patients with hypertensive with a sample of 139 as respondents by simple random sampling. Collecting data by questionnaires and Analysing data used Univariate and Bivariate (Chi-Square).Results: Finding that the patient has negative family support was 58.7%, the patient was noncompliant to a low-salt diet .57.2%, and few patients have an understanding of a low-salt diet. There is a relationship between the understanding of a low-salt diet (p-value = 0.000), family support (p-value = 0.032) and compliance with a low-salt diet among patients with hypertensive.Conclusion: There is a relationship of understanding of low-salt diets, family support and compliance to a low-salt diet among patients with hypertensive. Suggestions for  health workers in providing health education to families and patients with hypertensive about the importance of low salt diets in the management of hypertensionKeywords: Family support; Compliance; Understanding; Low-salt diet; Hypertensive. Pendahuluan: Hipertensi merupakan suatu gangguan pada pembuluh darah yang mengakibatkan suplai oksigen dan nutrisi yang dibawa oleh darah terhambat sampai ke jaringan tubuh yang membutuhkanya. Berdasarkan data dari Puskesmas Gedong Air, diketahui bahwa dari tahun 2015 – 2018 kejadian hipertensi mengalami fluktuatif , dimana tahun 2016 sebesar 1962 kasus namun di tahun 2017 mengalami peningkatan menjadi sebesar 2814 kasus dan di tahun 2018 kejadian hipertensi sebesar 3102 kasus.Tujuan: Diketahui hubungan dukungan keluarga, kepatuhan dan pemahaman  pasien terhadap diet rendah garam  pada pasien dengan hipertensiMetode: Penelitian kuantitatif dengan rancangan analitik dan pendekatan cross sectional, populasinya seluruh pasien dengan hipertensi dengan sampel sebanyak 139 dengan simple random sampling. Pengumpulan data dengan kuesioner data dianalisa secara univariate dan bivariate (chi square)Hasil: Diketahui dukungan keluarga kategori negatif 58,7%, responden tidak patuh 57,2%, dan sedikit yang memiliki pemahaman diet rendah garam  (p-value=0,000), ada hubungan antara dukungan keluarga (p-value = 0,032), kepatuhan dan pemahaman  pasien terhadap diet rendah garam  pada pasien dengan hipertensiSimpulan: Ada hubungan dukungan keluarga, kepatuhan dan pemahaman  pasien terhadap diet rendah garam  pada pasien dengan hipertensi. Saran bagi petugas kesehatan puskesmas dalam memberikan pendidikan kesehatan kepada keluarga dan pasien dengan hipertensi tentang pentingnya diet rendah garam.